3-T contrast-enhanced MR angiography with parallel imaging in cerebral venous and sinus thrombosis = Angiographie RM avec injection de gadolinium et imagerie parallèle à 3T pour l’étude des veines cérébrales et des thromboses veineuses - Lettau, Michael; Laible, Mona; Barrows, Robin Joyce; Heiland, Sabine; Bendszus, Martin; Hähnel, Stefan (Journal of neuroradiology, 2011)
Background and purpose - Contrast-enhanced (CE) 3D magnetic resonance venography (MRV) and CE 3D magnetization prepared rapid acquisition of gradient echo (MP-RAGE) sequences are increasingly commonly used methods for evaluation of the intracranial venous system. Our aim was to compare CE MRV, 2D time-of-flight (TOF) MRV and MP-RAGE sequences at 3 T for visualization of cerebral venous and sinus thrombosis. - Material and methods - Patients with suspected or known cerebral venous thrombosis were examined prospectively by TOF MRV, CE MRV and MP-RAGE sequences. In 11 consecutive patients (all women; mean age, 42.5 years; age range, 25-70 years) with venous thrombosis, scores according to overall image quality, and presence or absence (score P) and differentiation (score D) of venous thrombosis were evaluated. - Results - By all measurements, overall image quality ranged from good to excellent. In 20 of 52 venous structures (38.5%), score P was the same on TOF MRV, CE MRV and MP-RAGE sequences. Venous thrombosis was definitely or almost definitely present or absent with TOF MRV in 20 of 52 (38.5%), with CE MRV in 97 of 99 (97.9%) and with MP-RAGE sequences in 86 of 99 (86.9%) venous structures. In all venous structures with uncertain diagnosis on TOF MRV, thrombosis was definitely or almost definitely present or absent on CE MRV and MP-RAGE sequences. Differentiation of thrombosis was better on CE MRV (score D: 3.33) than on MP-RAGE sequences (score D: 2.78), followed by TOF MRV (score D: 1.32). - Conclusion - CE MRV was superior to TOF MRV and MP-RAGE sequences in visualizing cerebral venous and sinus thrombosis.
Gesehen am 17.08.2022